PENERAPAN SELF-REGULATED LEARNING PESERTA DIDIK TUNANETRA DI SEKOLAH INKLUSI - Annisa Rachman Budiana, - (2018)
Tunanetramemilikihambatandalampenglihatannya, yang berdampakpadapengalaman, mobilitasdaninteraksilingkungan.Meskipunberdampakpadavariasipengalaman, akantetapiadajugatunanetra yang memilikitingkatinteligensi normal danbahkanada yang di atas rata-rata anakawas. Kondisisaatini, pesertadidiktunanetralebihmemilihuntukmelanjutkanjenjangpendidikan di sekolahinklusi.Hal inimenjadikanpesertadidiktunanetraharusmampumengaturwaktubelajarnyadenganbaikbahkanketikaadakendala-kendala yang kurangmendukung.Tujuandaripenelitianiniadalahuntukmendeskripsikanpenerapanself-regulated learning pesertadidiktunanetra di sekolahinklusi. Metodepenelitianmenggunakanpendekatankualitatif, denganmetodedeskriptif.Subjekpadapenelitianiniberjumlahdua orang pesertadidiktunanetra yang berinisial FA dan BI.Jenisinstrumen yang digunakanadalahpedomanwawancara, pedomanobservasidanstudidokumentasi.Teknikpengumpulan data yang dilakukanadalahwawancara, observasi, danstudidokumentasi.Analisis data yang dilakukandilakukanadalahreduksi data, display data, danpenarikankesimpulan.Hasilpenelitianmenunjukkanbahwakeduasubjekmenerapkan 14 strategiself-regulated learning dalammengaturwaktubelajardanmenghadapihambatan yang dialami, sehinggamerekamampumencapaitujuan yang telahditetapkan. Penelitimerekomendasikan agar pesertadidiktunanetradapatmenggunakanself-regulated learning yang tepatdalambelajar, kemudiandalampembelajaranmatematika, sebaiknya guru menggunakan media pembelajaran yang konkrit. ---------------------- Blind has a visual impairment, which gives impacts to the experience, mobility, and environmental interaction. Despite giving impacts to the variation of experiences, there are several blinds who have the normal level of intelligence and even above the normal ones. In this situation, students with visual impairment prefer to continue their study in an inclusive school. It requires them to be able to manage their learning time well even if they find the obstacles. The aim of this study is to describe the implementation of students' with visual impairment self-regulated learning in an inclusive school. The method used in this study was qualitative approach, along with descriptive method. The subjects were two students with visual impairment, initialed as FA and BI. The research instruments were interview guidance, observational sheet, and documentary study. The techniques of collecting the data were interview, observation, and documentary study. The data analysis used in this study were data reduction, data display, and conclusion drawing. The result revealed that both subjects applied 14 strategies of self-regulated learning in managing their learning time and facing the obstacles, so that they could achieve their own goals. The researcher suggests that students with visual impairment can use the appropriate self-regulated learning. Moreover, in learning mathematic, it will be better to use the concrete learning materials.